Pharmacokinetics of Daptomycin in Pediatric Intensive Care Patients. (4th October 2017) - Antachopoulos, Charalampos; Kadiltzoglou, Paschalis; Ilia, Stavroula; Briassoulis, George; Geladari, Anastasia; Baira, Eirini; Gikas, Evangelos; Mylouli, Efstathia; Dokoumetzidis, Aristides; Volakli, Eleni; Sdougka, Maria; Roilides, Emmanuel
Abstract: Background: Daptomycin is a lipopeptide agent active against Gram-positive microorganisms, including methicillin-resistant Staphylococcus aureus and vancomycin-resistant enterococci. To date, only single dose pharmacokinetics (PK) has been studied in children. We studied multiple dose PK of daptomycin administered as salvage therapy in critically ill pediatric patients. Methods: Patients hospitalized in 2 pediatric intensive care units from June 2014 to December 2016, who received daptomycin for infections caused by Gram-positive organisms not responding or intolerant to conventional antimicrobial agents and had normal renal function, were eligible for the study. Daptomycin was administered as 30-minute infusion dissolved in 50 ml normal saline at dosages decided by the treating physicians. Blood samples were collected immediately before and 30, 60, 90, 120, 240, and 360 minute after the end of First and Fifth dose. Plasma concentrations of daptomycin were determined with ultra performance liquid chromatography. An individual pharmacokinetic model was built with WinNonlin version 6.4 (Certara, Princeton, NJ) software and a two compartment structural model was fit to daptomycin concentration data over time. Results: Four patients (2 females) of mean age 10.5 years (range: 8–14) and body weight 39 kg (range: 26–45), who received daptomycin at 10 mg/kg once daily (OD), were studied. The mean area under the curve of daptomycin concentrations at steady-state (AUC0–24 ) was 541.62 μg · hours/ml (range: 162.51–1001.71), with no significant differences compared with First dose. The mean clearance was 28.46 ml/hours/kg (range: 9.97–61.50), mean volume of distribution was 0.38 L/kg (range: 0.20–0.61), and mean t 1/2 was 13.4 hours (range: 8.3–20.1). Conclusion: The observed clearance and volume of distribution of daptomycin in critically ill children of mean age 10.5 years were significantly higher than those published for healthy adult subjects. A dose of 10 mg/kg OD of daptomycin in these patients resulted in comparable drug exposure (AUC) with that of adults receiving 4 mg/kg OD. Significant inter-patient variability was observed in daptomycin clearance and AUC, which may in part be due to the altered hemodynamic status of septic patients and warrants further investigation. Disclosures: All authors: No reported disclosures.